2017
DOI: 10.1136/bmjopen-2016-013724
|View full text |Cite
|
Sign up to set email alerts
|

Fall-related attendance and associated hospitalisation of children and adolescents in Hong Kong: a 12-year retrospective study

Abstract: ObjectivesThe present study aimed to examine the trends and characteristics of fall-related attendance in accident and emergency department (AED) by injury type and the trend in associated average length of stay (LOS) among children and adolescents in Hong Kong.DesignA retrospective approach was adopted.SettingAED, involving all local public emergency departments from 2001 to 2012.Participants63 557 subjects aged 0–19 years with fall injury record were included in the analysis.Primary outcome measuresFall-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
0
11
1
Order By: Relevance
“…Conversely, a recent population-based trend analysis of fall-related ED visits for fractures among children aged 0 to 19 years in Hong Kong reported that adjusted fracture rates increased at an annual percentage of 1.3% between 2001 and 2012, which contrast with the present study results. Although the reasons for the diverging trends found in this latter and our study remain to be elucidated, the overall upward trend in childhood ED visits for fall-related fractures in Hong Kong over the past decade may have been attributed to increased incidence of ankle/foot and wrist/hand fractures [8].…”
Section: Figure 3: Trends In Emergency Department Visits For Fall-relcontrasting
confidence: 53%
See 1 more Smart Citation
“…Conversely, a recent population-based trend analysis of fall-related ED visits for fractures among children aged 0 to 19 years in Hong Kong reported that adjusted fracture rates increased at an annual percentage of 1.3% between 2001 and 2012, which contrast with the present study results. Although the reasons for the diverging trends found in this latter and our study remain to be elucidated, the overall upward trend in childhood ED visits for fall-related fractures in Hong Kong over the past decade may have been attributed to increased incidence of ankle/foot and wrist/hand fractures [8].…”
Section: Figure 3: Trends In Emergency Department Visits For Fall-relcontrasting
confidence: 53%
“…Notably, ED visits for fall-related forearm/wrist fractures in children significantly decreased during the study period. Moreover, a marked annual decrease in fracture rates by 2.4 % was seen from 2004 onwards, which contrasts with those reported in Scandinavian countries, Hong Kong, and Olmsted County, Minnesota [6,8,12,13]. Indeed, a registry study from southern Sweden demonstrated that the age-standardized distal forearm fracture rate increased by 2.2% per year between 1999 and 2010.…”
Section: Figure 3: Trends In Emergency Department Visits For Fall-relmentioning
confidence: 75%
“…Similarly, admission to the ICU was significantly associated with chest, brain, abdomen and pelvis injuries, as well as other injuries. It has been reported that falls are the principal cause of non-fatal injuries among children and adolescents, contributing to 50% fall-related disability-adjusted life years (DALYs) lost worldwide [ 15 ]. It shows that the present study correlates with the previous literature in terms of most common fall-related injuries occurring amongst children and adolescents, which imposes a significant burden on healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“…According to the characteristics of injuries in different age groups, the government can implement targeted interventions in different crowds and then test the effectiveness of them [34]. For instance, to protect children from fall-related injuries, schools can install soft rubber and waterproof oor for schoolyards [35].…”
Section: Suggestions To Decision-makersmentioning
confidence: 99%